Rapid biosynthesis of N-doped TiO2 nanoparticles using plant extract of Tamarix sp.: Its antimicrobial, anti-oxidant activity and dielectric properties - Naqvi, Syed Mohd Adnan; Islam,Sk Najrul; Raza, Azam; Kshirsagar, Deepa; Chavan, Padmaja; Chankeshwara, Vishakha; Firdousi, Shakeel Ahmad; Ahmad , Absar (Next Materials, 2025)
<span style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Green synthesis is a technique for the fabrication of <a class="topic-link" href="https://www.sciencedirect.com/topics/chemical-engineering/nanoparticle" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;">nanoparticles (NPs) that is easy, eco-friendly, and emergent. It is currently garnering the attention of the scientific community worldwide since it is non-toxic, inexpensive, and reliable, and it takes place under ambient conditions. This research aimed to synthesize green N-doped <a class="topic-link" href="https://www.sciencedirect.com/topics/pharmacology-toxicology-and-pharmaceutical-science/titanium-dioxide-nanoparticle" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;">titanium dioxide nanoparticles (N-TiO<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif;">2<span style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">) and analyze their antimicrobial, anti-oxidant activity, and <a class="topic-link" href="https://www.sciencedirect.com/topics/materials-science/dielectric-property" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;">dielectric properties. A leaf extract of <span style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"><a class="topic-link" href="https://www.sciencedirect.com/topics/agricultural-and-biological-sciences/tamarix" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about Tamarix from ScienceDirect's AI-generated Topic Pages">Tamarix<span style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> sp. was used in a single step at <a class="topic-link" href="https://www.sciencedirect.com/topics/chemistry/ambient-reaction-temperature" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;">room temperature to fabricate N-TiO<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif;">2<span style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> <a class="topic-link" href="https://www.sciencedirect.com/topics/materials-science/nanoparticle" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;">nanoparticles with an average particle size of 26.5 nm. They were subsequently characterized by certain methods like Ultra Violet-Visible spectroscopy, <a class="topic-link" href="https://www.sciencedirect.com/topics/pharmacology-toxicology-and-pharmaceutical-science/transmission-electron-microscopy" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;">Transmission Electron Microscopy, <a class="topic-link" href="https://www.sciencedirect.com/topics/chemistry/field-emission-scanning-electron-microscopy" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;">Field Emission Scanning Electron Microscopy, X-ray diffraction, X-ray photoelectron spectroscopy, Fourier Transform Infra-Red Spectroscopy, etc. Moreover, the efficiency of the synthesized <a class="topic-link" href="https://www.sciencedirect.com/topics/pharmacology-toxicology-and-pharmaceutical-science/nanoparticle" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;">nanoparticles as antimicrobial agents was investigated against <span style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"><a class="topic-link" href="https://www.sciencedirect.com/topics/pharmacology-toxicology-and-pharmaceutical-science/bacillus-subtilis" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;">Bacillus subtilis<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">, <em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Escherichia coli<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> and <span style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"><a class="topic-link" href="https://www.sciencedirect.com/topics/agricultural-and-biological-sciences/aspergillus-niger" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;">Aspergillus niger<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">. Using 2, 2-diphenyl-1-picrylhydrazyl hydrate (DPPH), the antioxidant activity of synthesized N-TiO<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif;">2<span style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> <a class="topic-link" href="https://www.sciencedirect.com/topics/agricultural-and-biological-sciences/nanoparticle" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;">nanoparticles (NPs) was evaluated. UV–visible <a class="topic-link" href="https://www.sciencedirect.com/topics/chemical-engineering/spectrophotometry" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;">spectrophotometry was used to monitor the radical-scavenging activity of N-TiO<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif;">2<span style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> NPs. The <a class="topic-link" href="https://www.sciencedirect.com/topics/chemistry/dielectric-property" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;">dielectric properties were examined with the help of impedence analyzer and we observed high <a class="topic-link" href="https://www.sciencedirect.com/topics/chemistry/dielectric-constant" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;">dielectric constant and very low tangent loss.